KONSELING KELOMPOK DENGAN MENGGUNAKAN PENDEKATAN RATIONAL EMOTIVE BEHAVIOUR THERAPY DALAM MENGATASI PERILAKU SELF INJURY REMAJA: LITERATURE REVIEW - Afifah Bidayah; Netrawati; Yeni Karneli (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Self-injury is self-defeating behavior by intentionally hurting oneself to vent the psychological pressure experienced. To overcome this behavior, group counseling is used with a rational emotive behavior therapy approach. This approach is used to help teenagers change irrational thoughts into rational ones which will later be reflected in the form of behavior. This research uses literature study. And according to the studies that have been carried out, the rational emotive behavior therapy approach can overcome self-injury behavior in adolescents.